2013
DOI: 10.3122/jabfm.2013.04.120185
|View full text |Cite
|
Sign up to set email alerts
|

Follow-up After Telephone Consultations at Out-of-Hours Primary Care

Abstract: Background: After a contact with a primary care physician (PCP) cooperative for out-of-hours care, many patients have subsequent contact with health care. Little is known about the factors associated with these follow-up contacts. The objective of this study was to examine whether patient experiences with nurse telephone consultations and the cooperative's organizational characteristics were associated with the probability of follow-up contact.Methods :

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 21 publications
1
12
1
Order By: Relevance
“…We theorize that the reason for these findings may be related to elderly patients having multiple (including mobility) issues and would therefore be more likely to ensure that their concerns were fully resolved by the visiting AHHC doctors on each particular visit. This finding seems to differ somewhat from those a Dutch study published in 2013, which reported an increased probability of follow‐ups in patients aged 65 or over. This comparison should be made with caution, though, as the Dutch study focused on patients who used OOH telephone consultations, and not home visits.…”
Section: Discussion Conclusion and Recommendationscontrasting
confidence: 99%
See 2 more Smart Citations
“…We theorize that the reason for these findings may be related to elderly patients having multiple (including mobility) issues and would therefore be more likely to ensure that their concerns were fully resolved by the visiting AHHC doctors on each particular visit. This finding seems to differ somewhat from those a Dutch study published in 2013, which reported an increased probability of follow‐ups in patients aged 65 or over. This comparison should be made with caution, though, as the Dutch study focused on patients who used OOH telephone consultations, and not home visits.…”
Section: Discussion Conclusion and Recommendationscontrasting
confidence: 99%
“…Of equal interest is our finding that, after the AHHC consultations, 40.0% of the patients seen required no further follow‐ups (Table ), and this group were significantly more satisfied with the AHHC service on all scales of satisfaction (Table ). This latter observation is consistent with the report that patients with positive experiences of OOH consultations are less likely to require follow‐ups …”
Section: Discussion Conclusion and Recommendationssupporting
confidence: 92%
See 1 more Smart Citation
“…95 In particular, older patients were more likely to have follow-up contacts after receiving telephone advice. 114 The evaluation of NHS 111 pilot sites found no impact on attendances at EDs and contacts with urgent primary care services but a statistically significant increase in ambulance incidents. 105 Five studies found that the introduction of a telephone advice service for low-urgency ambulance service patients resulted in fewer ambulance responses being required.…”
Section: Service Impactsmentioning
confidence: 99%
“…Seventeen studies reported impacts on their own service or other services, either from increased or reduced service use and or increased or reduced staff workload [68][69][70]86,95,98,99,[101][102][103]105,109,112,114,122,126,134 One study found that NHS Direct referred a higher proportion of patients to other services when compared with general practice. 134 A RCT by Lattimer et al 68 reported a 38% reduction in primary care appointments and a 23% reduction in home visits, whereas another study reported no change in primary care appointments but home visits reduced by 18%.…”
Section: Service Impactsmentioning
confidence: 99%